Research on the non-point source pollution of microplastics - He, Li; Ou, Zhongwen; Fan, Jiangyang; Zeng, Boping; Guan, Wei (Frontiers in Chemistry, 2022)
Microplastics are characterized with universality, persistence and toxicity to aquatic organisms, the pollution of microplastics has attracted worldwide attention. At present, studies on microplastic pollution were mainly focused on the composition, abundance and species of microplastics in water bodies and sediments, and few studies were focused on the source and influence characteristics of microplastics in surface water bodies. Starting from the sources of microplastic pollution in surface water of this paper, the pollution status of agricultural microplastics was analyzed, and the importance and urgency of studying microplastic pollution in agricultural non-point sources were put forward. Therefore, it was intended to provide effective scientific basis and technical support for the control of microplastics non-point source pollution in river basins.